DETEKSI MOLEKUL MUTASI GEN rpoB MYCOBACTERIUM TUBERCULO SIS PADA DAHAK DENGAN POL YME RASE CHAIN REACTION DAN SINGLE STRAND CONFORMATION POLYMORPHISM - P B Notopuro; J Nugraha; H Notopuro (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Tuberculosis is a chronic infectious disease which is found in the developing as well as the developed country. This disease is oneof the community health problems which become the priority programs in the national as well as international health. In the lasttwo decades, they can be found in the emergency tuberculosis problems that is related with the Multi Drug Resistance (MDR) Strain.The detection of rifampicin resistance in M. tuberculosis infection can help clinical laboratory to find the MDR strain. Related to thisproblem the proportional culture method is still the gold standard for rifampicin resistance detection for M. tuberculosis infection. Butthis method needs 4−6 weeks to obtain the result, while its sensitivity is not very high. The development of the molecular detection forM. tuberculosis rifampicin resistance in a direct clinical specimen such as sputum, cerebrospinalfLuid, etc. will give an improvement inthe diagnosis, because it has an accurate, fast, sensitive and a specific result. Isolates from twenty six of M. tuberculosis derived fromthe sputum of tuberculosis patients that have failed the tuberculosis treatment, were examined with the proportional culture method.In this study PCR-SSCP were used for the molecular detection of rifampicin resistancy using direct sputum samples. The proportionalculture method was used as a gold standard for the rifampicin resistance detection. A set of primers was directed to conserve the regionof rpoB gene of M. tubercuLosis. This RNA polymerase gene was encondes?, which is bound on rifampicin. A 157-bp fragment wasamplified by PCR and analyzed by SSCP technique. The sensitivity of PCR-SSCP is 80% (high), its specificity is 95.2% (very high), thepositive predictive value is 80% and the negative predictive value is 95.2%. Statistically there were no significant difference between theresult of PCR-SSCP and the proportional culture method. Based on the study result, the molecular detection technique for rifampicinresistance on M. tuberculosis infection can be used as the screening device /means for Multi Drug Resistance Tuberculosis (MDR-TB),while the clinician waits the culure result.